Dengue Viral Infection Induces Alteration of CD95 Expression in B Cell Subsets with Potential Involvement of Dengue Viral Non-Structural Protein 1 - Siyu Wang; Premrutai Thitilertdecha; Ladawan Khowawisetsut; Theeraporn Maneesawat; Ampaiwan Chuansumrit; Kulkanya Chokephaibulkit; Kovit Pattanapanyasat; Nattawat Onlamoon (Viruses)
Little is known about the regulation of B cell subpopulations in association with programmed cell death during dengue virus (DENV) infection. Therefore, blood samples from dengue-infected patients and healthy donors were obtained for B cell subset characterization and the analysis of pro-apoptotic CD95 expression in these cell subsets. The results showed that the activated memory (AM) subset in the patients remained unchanged compared to the healthy donors. In contrast, tissue memory (TM) and antibody-secreting cells (ASCs) were notably increased, whereas naïve cells and resting memory (RM) cells were considerably decreased. Although the ASCs maintained comparably high levels of CD95 expression in both groups, significantly increased percentages of CD95-expressing cells in the other B cell subsets were found in the patients. When B cells from the healthy donors were treated with DENV non-structural protein 1 (NS1), the results showed that the NS1 protein at 2 µg/mL could induce CD95 expression and the exposure of phosphatidylserine on the cell membrane in most B cell subsets, except for the RM. This study demonstrates that DENV infection could induce CD95 expression in both activated and resting B cell subsets in all patients. The results also suggest a potential mechanism of apoptotic regulation in B cell subsets through the increased CD95 expression caused by the interaction between the B cells and the NS1 protein.